Antidiabetic and Antihyperlipidemic Activity of Ethanolic Extract of Mentha viridis in Alloxan Induced Diabetic Rats - Juthy, Nusrat Jahan; Islam, Gazi Jahirul; Zehad, Abdullah; Zannah, Shaheda (Sciences of Pharmacy, 2024)
This research was designed to examine the phytochemicals of Mentha viridis (M. viridis) ethanolic extract and the antidiabetic and antihyperlipidemic activities in alloxan-induced animal models. Diabetes was induced chemically by administering a unit dose of alloxan at 120 mg/kg BW. After alloxan induction, hyperglycemic rats were dealt with ethanolic extract of leaf and whole plant, metformin, and a mixture of leaf extract with metformin and whole plant extract with metformin for two weeks. Ethanolic extract of leaf and whole plant, metformin, and a combination of both leaf and whole plant extract with metformin therapies reduced glucose levels in the blood compared with the diabetic negative control group after two weeks of treatment. However, among the therapies, the ethanolic leaf extract and the combination of whole plant extracts with metformin were found to be the most effective (p<0.05), with reductions of 62.82% and 72.89%, respectively. After diabetes induction, the serum level of TG (triglycerides), TC (total cholesterol), LDL-C (low-density lipoprotein-cholesterol) escalated notably (p<0.05), and HDL-C (high-density lipoprotein-cholesterol) level decreased remarkably (p<0.05) in hyperglycemic rats as opposed to healthy normal rats. Ethanolic leaf extract and a combination of whole plant extract with metformin significantly minimized the elevated extent of TG and LDL-C. They surged HDL-C, but the TC level was reduced by whole plant extract only after two weeks of treatment. The standard procedures were used to identify the phytochemical compounds of the medicinal plant M. viridis. The phytochemical compounds such as alkaloids, resins, tannins, phenols, flavonoids, steroids, and terpenoids appeared in the ethanolic leaf extract of M. viridis. The findings suggest that M. viridis might provide better glycemic control and hypolipidemic effect in diabetic rats when administered alone or combined with oral antidiabetic agents. Incorporating M. viridis extract with metformin in improving hyperglycemic and hyperlipidemic conditions in diabetic rats proves that M. viridis has a synergistic effect, which could enhance the antidiabetic activity of oral hypoglycemic agents.